Peut-on contribuer a l’epanouissement interculturel des apprenants de fle a travers I ’organisation des echanges scolaires - Orchowska, Izabela (Glottodidactica, 2001)
In this article, we would like to show that participation in school exchanges can contribute to the development of foreign language learners' intercultural competence. To begin with, we shall analyse challenges of intercultural education in a theoretical way. Secondly, we shall present our own research connected with a school exchange between Polish and French learners which was organised in 1999. In this presentation we shall emphasise the influence of the circumstances in which the exchange took place on the evolution of intercultural competence.